ICIRAS: Research and reconciliation with indigenous peoples in rural health journals. (20th July 2022) - Lock (Ngiyampaa), Mark J.; McMillan (Wiradjuri), Faye; Warne (Oglala Lakota), Donald; Bennett (Gamilaraay), Bindi; Kidd (Ngāpuhi), Jacquie; Williams (Bkejwanong), Naomi; Martire, Jodie Lea; Worley, Paul; Hutten‐Czapski, Peter; Saurman, Emily; Matthews (Quandamooka), Veronica; Walke (Bundjalung), Emma; et al.
Abstract: Aim: We aim to promote discussion about an Indigenous Cultural Identity of Research Authors Standard (ICIRAS) for academic journal publications. Context: This is based on a gap in research publishing practice where Indigenous peoples' identity is not systematically and rigorously flagged in rural health research publications. There are widespread reforms, in different research areas, to counter the reputation of scientific research as a vehicle of racism and discrimination against the world's Indigenous peoples. Reflecting on these broader movements, the editorial teams of three rural health journals—the Australian Journal of Rural Health, the Canadian Journal of Rural Medicine, and Rural and Remote Health—recognised that Indigenous peoples' identity could be embedded in authorship details. Approach: An environmental scan (through a cultural safety lens where Indigenous cultural authority is respected, valued, and empowered) of literature was undertaken to detect the signs of inclusion of Indigenous peoples in research. This revealed many ways in which editorial boards of Journals could systematically improve their process so that there is 'nothing about Indigenous people, without Indigenous people' in rural health research publications. Conclusion: Improving the health and wellbeing of Indigenous peoples worldwide requires high quality research evidence. The philosophy of cultural safety supports the purposeful positioning of Indigenous peoples within the kaleidoscope of cultural knowledges as identified contributors and authors of research evidence. The ICIRAS is a call‐to‐action for research journals and institutions to rigorously improve publication governance that signals "Editing with IndigenUs and for IndigenUs".